2012
DOI: 10.14419/ijamr.v1i4.206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hall Current on Hydromagnetic Natural Convection Flow of a Heat Absorbing Fluid past an Impulsively Moving Vertical Plate with Ramped Temperature

Abstract: Effects of Hall current on unsteady MHD natural convection flow of a viscous, incompressible, electrically conducting and heat absorbing fluid past an impulsively moving vertical plate with ramped temperature in a porous medium, in the presence of thermal diffusion, is studied. The exact solution of momentum and energy equations, under Boussinesq approximation, is obtained in closed form by Laplace transform technique for both ramped temperature and isothermal plates. Solution is also obtained in the case of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Seth and Ansari [36] investigated unsteady hydromagnetic natural convection flow of a viscous, incompressible, electrically conducting and heat absorbing fluid past an impulsively moving vertical plate with ramped temperature embedded in a fluid saturated porous medium taking into account the effect of thermal diffusion. Subsequently, Seth et al [37] considered the effects of Hall current on the problem studied by Seth and Ansari [36]. Patra et al [38] considered the effects of radiation on natural convection flow of a viscous and incompressible fluid near a stationary vertical flat plate with ramped temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Seth and Ansari [36] investigated unsteady hydromagnetic natural convection flow of a viscous, incompressible, electrically conducting and heat absorbing fluid past an impulsively moving vertical plate with ramped temperature embedded in a fluid saturated porous medium taking into account the effect of thermal diffusion. Subsequently, Seth et al [37] considered the effects of Hall current on the problem studied by Seth and Ansari [36]. Patra et al [38] considered the effects of radiation on natural convection flow of a viscous and incompressible fluid near a stationary vertical flat plate with ramped temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Since Hall current tends to induce a secondary flow in the flow-field (Sutton and Sherman, 1965), it plays a crucial role in defining the flow-field characteristics. Due to the huge importance of such physical effect, Pop and Watanabe (1994), Aboeldahab and Elbarbary (2001), Seth et al (2013 and Das et al (2013) investigated the influence of Hall current on hydromagnetic natural convection flow near a vertical plate, considering various aspects of the problem. Reddy (2014) considered Hall effect, thermal radiation and viscous dissipation on MHD convective flow of a viscous, electrically conducting and incompressible fluid past a stretched vertical sheet.…”
Section: Introductionmentioning
confidence: 99%
“…studied the Hall and ion-slip effect on boundary layer flow of a micro polar fluid past a wedge in presence of magnetic field and concluded that in a micro polar fluid, the Hall effect and increased magnetic field enhances the heat transfer rate significantly. Seth et al (2015aSeth et al ( ), (2015b and (2015c) also studied the Hall current effects on hydromagnetic convection flow under different heat generation/absorption conditions. Magneto hydrodynamic stagnation point flow and heat transfer on stretching sheet with chemical reaction and transpiration is studied by Mabood et al (2015).…”
Section: Introductionmentioning
confidence: 99%